Specificity of Managerial Consultancy for SMEs and its Status in Romania. (7th June 2016) - Nicolescu, Ovidiu; Nicolescu, Ciprian
Abstract: Due to the fact that SMEs are the engine of economic growth in most countries of the world, and their performances are impacted more and more by appealing to consultancy services, highlighting the specificity of management consultancy for SMEs and its status in Romania is of particular importance. This paper approaches the concept of managerial-entrepreneurial consultancy, situations and requirements of SMEs for consultancy, selection of consultant and consultancy negotiation, stages of managerial-entrepreneurial consultancy, and status of entrepreneurial-managerial consultancy in Romania. It ends with formulating a set of recommendations in order to increase professionalism and performance of management consultancy in Romania